Alphaworld: after the storm - Schembri, Tess (Oxford University Press Melbourne, 2004)
After the storm, the world feels refreshed and renewed. The air is crisp, carrying the scent of damp earth and freshly washed leaves. Puddles collect in low spots, reflecting the clear blue sky and the bright sunlight breaking through the clouds. Birds begin to chirp again, filling the silence with their cheerful songs. The landscape is transformed; trees stand tall, glistening with raindrops, while flowers bloom more vibrantly than before. People emerge from their homes, sharing stories of the storm$1 (Bs intensity, while children splash joyfully in the puddles. It$1 (Bs a moment of calm and clarity, reminding us of nature$1 (Bs resilience and the beauty that often follows turbulence.s